ANTIBACTERIAL AND OSTEOINDUCTIVE DENTAL IMPLANT SURFACE NANOPARTICLE COATINGS - A.V. BLINOVA; A.A. AVAKYAN; I.V. KOROLYOV; I.A. TROFIMOV (Паёми Сино, 2025)
The increase in the total number of dental implants installed has led to a rise in the percentage of losses due to inflammatory complications, such as peri-implantitis and peri-implant mucositis. To enhance the predictability of treatment and stimulate the biological processes responsible for implant integration, researchers are developing dental implants with modified surfaces. The primary focus of advancing implantology involves creating technologies that ensure high biocompatibility between bioinert titanium implants and the surrounding tissues. This goal can be achieved, for example, by designing a particular surface microrelief or by incorporating biologically active signaling molecules such as amino acids, peptides, and nucleotides. Additionally, researchers are developing coatings that aim to inhibit the activity of pathogenic microorganisms and prevent the formation of microbial biofilms. This aim is often accomplished through the biocidal properties of nanoparticles derived from metals and organic compounds, including chitosan and graphene.